2015
DOI: 10.1002/ajh.24028
|View full text |Cite
|
Sign up to set email alerts
|

A single high‐resolution HLA mismatch has a similar adverse impact on the outcome of related hematopoietic stem cell transplantation as a single low‐resolution HLA mismatch

Abstract: The relative importance of the resolution level of HLA typing has not been fully defined for related donor transplantation. To address this question, we retrospectively evaluated patients who underwent a first related hematopoietic stem cell transplantation (HSCT) from 2000 to 2011 from an HLA high‐resolution matched (MRD, n = 2,244), high‐resolution 1 locus‐mismatched (HR‐MMRD, n = 116), or low‐resolution 1 locus‐mismatched related donor (LR‐MMRD, n = 396) in the graft‐versus‐host direction at three loci (HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Recently, it has been shown that both high-resolution HLA typing and haplotyping are important in hematopoietic stem cell transplantation for both unrelated and related donors in reducing post-transplantation adverse outcomes (Agarwal et al, 2017;Buhler et al, 2019); a single high-resolution HLA mismatch may lead to a similar negative effect on outcomes as a low-resolution one (Fuji et al, 2015;Armstrong et al, 2017). Therefore, it has been suggested that highresolution HLA typing can reduce the likelihood of missing a clinically significant mismatch compared to traditional lowresolution typing, especially in developing countries where highresolution HLA typing methods are not widely available (Agarwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that both high-resolution HLA typing and haplotyping are important in hematopoietic stem cell transplantation for both unrelated and related donors in reducing post-transplantation adverse outcomes (Agarwal et al, 2017;Buhler et al, 2019); a single high-resolution HLA mismatch may lead to a similar negative effect on outcomes as a low-resolution one (Fuji et al, 2015;Armstrong et al, 2017). Therefore, it has been suggested that highresolution HLA typing can reduce the likelihood of missing a clinically significant mismatch compared to traditional lowresolution typing, especially in developing countries where highresolution HLA typing methods are not widely available (Agarwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The standard pharmacological GVHD prophylaxis regimen for HLA‐matched unrelated (MUD) or related donor (MRD) HCT includes a calcineurin inhibitor (commonly tacrolimus or ciclosporin) and methotrexate (Nash et al , ; Hiraoka et al , ; Perkins et al , ; Saber et al , ). This is often intensified with in vivo T‐cell depletion (TCD), generally with antithymocyte globulin (ATG) or alemtuzumab in MMUD HCT (Finke et al , ; Ayuk et al , ; Devillier et al , ; Fuji et al , ). With this intensive regimen, the incidence of grade II–IV acute GVHD (20–35%), grade III–IV acute GVHD (4–20%) and chronic GVHD (22–67%) in MMUD HCT approaches comparable levels to those seen after MUD HCT (Finke et al , ; Ayuk et al , ; Kim et al , ; Devillier et al , ; Fuji et al , ).…”
mentioning
confidence: 99%
“…This is often intensified with in vivo T‐cell depletion (TCD), generally with antithymocyte globulin (ATG) or alemtuzumab in MMUD HCT (Finke et al , ; Ayuk et al , ; Devillier et al , ; Fuji et al , ). With this intensive regimen, the incidence of grade II–IV acute GVHD (20–35%), grade III–IV acute GVHD (4–20%) and chronic GVHD (22–67%) in MMUD HCT approaches comparable levels to those seen after MUD HCT (Finke et al , ; Ayuk et al , ; Kim et al , ; Devillier et al , ; Fuji et al , ). However, in vivo TCD delays T‐cell immune reconstitution (Small et al , ; Duval et al , ; Bosch et al , ) and poses heightened risk of bacterial and viral infections, including herpes simplex virus, cytomegalovirus (CMV), Epstein–Barr virus, and infection‐related deaths (Bacigalupo et al , ), as well as fatal post‐transplant lymphoproliferative disorder (PTLD) (Small et al , ; van Esser et al , ; Finke et al , ).…”
mentioning
confidence: 99%
“…The role of allelic mismatching at HLA-DPB1 in HSCT appears to be complex as it is related to expression level 23 and so called permissive and non-permissive mismatch groups 22 , 27 , 28 . It is also known that even a single allelic mismatch at HLA can induce an alloimmune response 29 , 30 , including graft-versus-leukemia effect, a favourable phenomenon that reduces the risk of relapse 31 , 32 . Hence, our finding that the number of mismatched nucleotides correlates with the GvHD risk fits well to these findings.…”
Section: Discussionmentioning
confidence: 99%